Inheritance of Neural Substrates for Motivation and Pleasure. (August 2019) - Li, Zhi; Wang, Yi; Yan, Chao; Cheung, Eric F. C.; Docherty, Anna R.; Sham, Pak C.; Gur, Raquel E.; Gur, Ruben C.; Chan, Raymond C. K.
Despite advances in the understanding of the reward system and the role of dopamine in recent decades, the heritability of the underlying neural mechanisms is not known. In the present study, we examined the hemodynamic activation of the nucleus accumbens (NAcc), a key hub of the reward system, in 86 healthy monozygotic twins and 88 healthy dizygotic twins during a monetary-incentive-delay task. The participants also completed self-report measures of pleasure. Using voxelwise heritability mapping, we found that activation of the bilateral NAcc during the anticipation of monetary gains had significant heritability ( h 2 = .20–.49). Moreover, significant shared genetic covariance was observed between pleasure and NAcc activation during the anticipation of monetary gain. These findings suggest that both NAcc activation and self-reported pleasure may be heritable and that their phenotypic correlation may be partially explained by shared genetic variation.